Gambaran Perilaku Remaja Tentang Seksual Pranikah di SMK PGRI Ciumbuleuit Bandung - Andini, Andini H; Efrasianty, Efrasianty N; Handiana, Handiana T (JURNAL KESEHATAN KARTIKA, 2019)
Sexual behavior is a behavior that driven by sexual desire with opposite sex or same sexwithout legitimate marriage .One of the factor that influence the premarital sexual behavior isgender .The research purpose is to know the adolescent behavior about premarital sexual atSMK PGRI Ciumbuleuit Bandung. The method is descriptive with 50 respondents. Thesampling is total sampling. The data was taken by questionnaire data analysis was presentedby frequency distribution the result is mostly of adolescent have good behavior (76%), andthe others have not good behavior (24%). The boys have good behavior as much as 38% and,the other boys have not good behavior 8%, the girls have good behavior 8%, The girls havegood behavior as much as 23 persons (8%). The other girls have not good behaviour as muchas 38% The recommendation for the school improve the knowledge and have attention tostudents to avoid premarital sexual behaviour especially at SMK PGRI Ciumbuleuit Bandung and do counselling about premarital sexual to improve the knowledge as information materialfor teacher to avoid the premarital sexual in adolescent.